How does educational attainment affect self-rated health among middle-aged and older adults in China? The role of leisure participation and Hukou system - Kang Jia; Fang Yuan; Kai-Peng Gan; Yuan-Ni Yang (BMC Public Health)
Abstract Amid the global phenomenon of population aging, the health of middle-aged and older adults has become an increasingly critical concern in Chinese society. Drawing on data from the 2021 China General Social Survey (CGSS), this study examines the impact of educational attainment on self-rated health among middle-aged and older adults in China, as well as the mechanisms through which leisure participation and Hukou system (household registration) affect this relationship. The results reveal that leisure participation partially mediates the relationship between education and self-rated health. Furthermore, Hukou system is found to negatively moderate both the direct effect of education on leisure participation and the indirect effect of education on self-rated health through leisure participation. These results provide new understanding of the mechanisms by which education impacts the health of middle-aged and older adults, offering important policy implications for tackling the challenges associated with an aging population.